Physical properties of palm kernel cake - Shakirin, Faridah Hanim; Abdullah, Norhani; Liang, Juan Boo; Mohamed Mustapha, Noordin (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
A systematic sieving method (500 g sample; 50 Hz, 20 min) was used to obtain mean sizes of 6.38, 3.72, 2.40, 1.50, 0.75, 0.40, 0.15mm of palm kernel cake (PKC). The highest mass percentage was 20.9% for 0.15 mm particle size. The lowest mass percentage of 7.6% was observed for 2.40 mm particle size. The mean particle size of PKC was 1.79±0.09 mm. The swelling capacity and water retention capacity of different particle sizes of PKC ranged from 2.13 to 3.81 ml/g dry matter and 1.98 to 2.66 g/g dry matter of sample, respectively. The highest protein content was observed in 0.40 mm particle size while the lowest was in 1.50 mm. The ash, crude fat and crude fiber contents were significantly (P<0.05) different among particle sizes of PKC.